Nanoliter‐Droplet Acoustic Streaming via Ultra High Frequency Surface Acoustic Waves. (27th March 2014) - Shilton, Richie J.; Travagliati, Marco; Beltram, Fabio; Cecchini, Marco
<x xml:space="preserve">Abstract</x> The relevant length scales in sub‐nanometer amplitude surface acoustic wave‐driven acoustic streaming are demonstrated. We demonstrate the absence of any physical limitations preventing the downscaling of SAW‐driven internal streaming to nanoliter microreactors and beyond by extending SAW microfluidics up to operating frequencies in the GHz range. This method is applied to nanoliter scale fluid mixing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>